Coesão e fé: das estratégias de coesão textual às manifestações da fé sintético-convencional presentes nas cartas pessoais produzidas na escola - Bispo, Luciana Santos (2013)
This work presents the results of a field research carried out with adolescents. The goal was to comprehend the strategies of referential cohesion and the characteristics of the conventional-synthetic faith in letters produced in the school. Based on the textual production of students the research revealed that the pronominal anaphoras and the ellipses were the resources of referential cohesion which were most used as collaborating linguistic elements in the construction of the textual fabric. With regard to the faith of the adolescent, it was observed with this research that, in fact, they are living stage 3 of the faith, that is, the conventional-synthetic faith postulated by James Fowler; being as one can identify in all the letters produced the presence of at least four of the five characteristics presented by the referred author as representative of this stage of the faith characteristic of adolescents. That is: in adolescence the image of God becomes more personal, more intimate; the identity of the adolescent youth is molded by the groups to which they belong (family and religious community). Adolescents have within them a model of faith, inherited from the family, from the groups in which they are involved, in other words, it is a non-analyzed faith and the expectation, in this phase of life, is centered on the external authority. The research also revealed that the adolescents use the faith they have as strategies for life cohesion. Thus they find in the faith the hope and courage to overcome challenges, undertake struggles to draw objectives and goals always trusting in the existence of the Transcendent, in this case, represented by the figures of God and/or Jesus Christ, who drives them, above all, to believe in the power of the faith and to live according to what they profess.